The emerging role of the urban-based Aboriginal peer support worker: A Western Australian study - Munns, Ailsa; Toye, C.; Hegney, D.; Kickett, M.; Marriott, R.; Walker, R. (Elsevier BV, 2016)
Purpose: To explore the self-perceived role of the Aboriginal peer support worker working with families with young children. This study was a component of a larger participatory action research study undertaken in a Western Australian metropolitan setting to develop and evaluate the suitability, feasibility and effectiveness of an Aboriginal peer-led home visiting program. Methods: Focus group interviews were carried out with peer support workers using unstructured and semi-structured interviews within Action Learning Sets. Data were analysed using thematic analysis. Results: The overarching theme on the self-perceived role of the Aboriginal peer support worker was Giving Parent Support, with subsidiary themes relating to development and ongoing sustainability of the support. Discussion: The peer support workers viewed their role as providing parent support through enabling strategies which developed client acceptance and trust, delivered culturally relevant support, advocated for families, developed therapeutic engagement and communication strategies, and created safe home visiting practices. They recognised the importance of linking families with community support such as community child health nurses which was important for improving long term physical and psychosocial health outcomes for children. Conclusion: Aboriginal Peer Support Workers identified their emerging integral role in the development of this unique culturally acceptable home visitingsupport for Aboriginal parents. Innovative approaches towards client engagement demonstrated their value in developing creative ways of working in partnership with families, community support services and child health nurses across a range of challenging psychosocial environments.